Bantuan Hukum Sebagai Hak Warga Negara Yang Dijamin Negara Berdasar Undang-Undang - Nina Zainab; Sarman (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The understanding of obtaining legal aid is not yetfully understood by citizens in general, including inmates asprisoners who are currently undergoing a case examinationprocess as subjects who are in conflict with the law. This legaleducation aims to ensure that inmates, especially detainees ontrial, can understand the function of legal aid and their rights toobtain legal aid. In this counseling, the inmates are participants,in this case the inmates/inmates who previously did not fullyunderstand their function and rights to legal aid, can understandit clearly. It is hoped that participants will immediately exercisetheir right to obtain legal assistance when facing investigationsinto criminal cases against each of them. This activity wascarried out using the face-to-face offline method at the PondokBambu Detention Center. The resource person is a lecturer fromBhayangkara University, Greater Jakarta, conducting outreachby visiting the PondokBambu Detention Center.